1985
DOI: 10.1007/bf02541905
|View full text |Cite
|
Sign up to set email alerts
|

Isoricinoleic acid inAnnona squamosa seed oil

Abstract: Annona squamosa seed was found to contain 23% oil, of which 9.8% was a hydroxy acid. After isolation from the other acids using silica gel column chromatography, it was identified as isoricinoleic acid. The fatty acid composition and analytical data on the oil are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…There is no research data, as far as we know, available in the oil content of C. nilotica seed. The oil content of A. squamosa kernels in this study was higher than that reported by Ansari et al [8] who reported 23% oil content, but it was in the range of 14-49% which was reported by Morton in 1987 [7]. The oil content of C. nilotica kernels was higher than most Sudanese conventional oilseeds (cottonseed, sunflower and groundnut), while that of A. squamosa was lower than that of cottonseed, sunflower, sesame and groundnut [25].…”
Section: Resultscontrasting
confidence: 86%
See 2 more Smart Citations
“…There is no research data, as far as we know, available in the oil content of C. nilotica seed. The oil content of A. squamosa kernels in this study was higher than that reported by Ansari et al [8] who reported 23% oil content, but it was in the range of 14-49% which was reported by Morton in 1987 [7]. The oil content of C. nilotica kernels was higher than most Sudanese conventional oilseeds (cottonseed, sunflower and groundnut), while that of A. squamosa was lower than that of cottonseed, sunflower, sesame and groundnut [25].…”
Section: Resultscontrasting
confidence: 86%
“…Differences in the fatty acid composition of the seed oil may exist even within the same variety. For example, Ansari et al [8] and Ahmad et al [27] reported that the dominant fatty acids in the seed oil of A. squamosa Linn. were oleic (37.0%), palmitic (25.1%) and linoleic (10.9%).…”
Section: Fatty Acid Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ansari et al (1985), the seed oil of A. squamosa occurring in India is characterized by a high content of isoricinoleic acid (9.8%). Up to now, the cited publication is the only one that describes the occurrence of isoricinoleic acid in the Annonaceae family.…”
mentioning
confidence: 99%
“…Seeds from both samples had similar oil content at 22-23 %. Seed kernels from Annona squamosa (sugar apple) have previously been reported to be a source of IR at close to 10 % of total seed fatty acids [11]. More recent studies have failed to identify IR in this species with oleic (18:1 Δ9 , 40 %) and linoleic (18:2 Δ9,12 , 29 %) as the dominant acyl components and an oil content of 24 % [25].…”
Section: Seed Acyl Compositionmentioning
confidence: 99%